(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This work explores how Eastern and Western philosophical traditions interpret human nature. In Eastern thought, the human being is often understood in harmony with society, morality, and spiritual balance, while Western views frequently focus on individuality, rationality, and the struggle between personal freedom and social order. The study highlights similarities and differences in these perspectives, showing how cultural, religious, and historical contexts shaped them. It also emphasizes the relevance of these ideas for modern society and their influence on education, ethics, and personal development.